Conceptual model of psychological reactance level on personalization advertisement toward advertising avoidance in social media platforms - Muhammad Zayyan Nurfauzi; Rafiati Kania (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Customizing advertising on social media currently become burgeoning practice. The progress of the current advertising system is also supported by the ease of retrieving digital data so that the collection of Personal Identifiable Information (PII) can be done more intensely. Many studies have done research on the effect of the level of personalization on the reactance level toward the intention to avoid the advertising. This study aims to conceptualize the antecedent motives of psychological reactance level toward consumer advertising reactance, namely ads avoidance. This study has done reviewing several works of literature on social media advertising reactance (SMAR) studies and formulated a conceptual model to be used for future research direction. This study adds data privacy security as a model novelty. As a result, three antecedent motives such as information quality, relevance, and control hypothesized to draw the level of psychological reactance in avoiding social media advertising.